LMO7-ALK Fusion in a Lung Adenocarcinoma Patient With Crizotinib: A Case Report - Yang, Yanlong; Zheng, Hongbo; Li, Zizhe; Shi, Shuchen; Zhong, Lang; Gong, Longlong; Lan, Bin (Frontiers in Oncology, 2022)
Background: Rearrangements of anaplastic lymphoma kinase (ALK) gene comprise a small subset of non-small cell lung cancer (NSCLC). Patients with NSCLC harboring ALK fusion proteins are sensitive to ALK tyrosine kinase inhibitors (TKIs). Various fusion partners of ALK are being discovered with the application of next-generation sequencing (NGS). Case presentation: Here we report a female patient with metastatic lung adenocarcinoma harboring LMO7-ALK (L15, A20) rearrangement revealed by NGS. The patient received crizotinib as first-line treatment and has achieved partial response with a progression-free survival over one year. Conclusions: We firstly found that the satisfactory response to crizotinib verified the oncogenic activity of LMO7-ALK fusion. Great progression and widely application of NGS facilitate the findings of rare fusion types.